Dietary and Lifestyle Changes Reverses Hypertension Rapidly (P16-020-19). (13th June 2019) - Krueger, Amy; Sanchez, Albert; Shavlik, Jerry; Ramirez, Francisco; Lukans, Richard; Bivens, Randy; Brown-Fraser, Sherine
Abstract: Objectives: Hypertension increases cardiovascular disease mortality; it is worldwide; and it is the number one cause for medical interventions in the U.S. We tested the effectiveness of reversing systolic blood pressure (SBP) in older adults by an intensive lifestyle of a wholefoods vegan diet together with other health principles of the Adventist Lifestyle that prevents hypertension. Methods: This is a retrospective 2-week pretest-posttest analysis in 1132 hypertensive men and women (mean ± SD: 64.0 ± 12.3, SBP 143 ± 22 mmHg) enrolled consecutively from 1988 to 1999 in an 18-day medically operated health improvement program, NEWSTART (Nutrition, Exercise, Water, Sunlight, Temperance—moderation and no addictive substances as tobacco or alcohol—fresh Air, Rest, and Trust [spirituality/relationships]). The whole-foods vegan diet had 26% of energy as fat and 1193 mg sodium/1000 calories. Data was analyzed by paired t-test using SPSS Statistics. Results: SBP dropped significantly ( P < 0.001) in the entire population within 18 days from 142 ± 0.8 to 119 ± 1.4–23 (−23 mmHg or −16%). Diastolic blood pressure dropped -14%. SBP pressure decreased in all subgroups ( P < 0.001): men −13% or women −15%; not taking (−19%) or taking antihypertensive medications (−11%); and normal (−15%) or excess weight (−14). SBP decreased to <120 mmHg in 68% of the population. Most of the subjects decreased or discontinued the use of antihypertensive medications. Conclusions: The intervention reversed systolic and diastolic blood pressure rapidly and two thirds of the subjects were no longer hypertensive within 18 days. SBP decreased as rapidly as has been reported for intensive medication therapy that provokes serious side effects. It decreased SBP while antihypertensive medications were being decreased or discontinued by most subjects. The intervention with a whole-foods vegan diet containing moderate levels of fat and salt is effective as a first line treatment of hypertension as recommended by the evidence-based guideline for adults reported by the VIII Joint National Committee (JNC8). Funding Sources: Self funded.